Female Labor Markets in Santiago de Chile: rising middle class (Revista LIDER, 2021)
The globalization of world economies has led to a great diversity of economic transformations', with particular effects upon the structure of labor markets, where, in addition, the feminine participation rates and the presence of socio-occupational middle groups have increased significantly. In parallel, the city has expanded towards the periphery and new centers have appeared within its radius, increasing the already acute segregation and exclusion characteristic of large cities in developing countries. This article analyzes these processes, emphasizing the location patterns of different socioeconomic groups and focusing especially on women.